Managing Web-based data - database models and transformations - Atzeni, P.; Mecca, G.; Merialdo, P. (IEEE internet computing, 2002)
The paper considers the Araneus data model which employs database techniques and wrappers to extract data from and generate Web sites. The project features a logical model that abstracts physical aspects of Web sites. Araneus provides high-level descriptions of pages that let us both extract data from the Web and generate Web sites from databases.